Assessment on the Service System on Selected Fastfood Chain at SM Fairview Novaliches, Quezon City: A Basis for Enhancement: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Intro Good service is one of the most essential in the Food and beverages industry, andTechnology is unquestionably one of the factors that contribute to high-quality service; withoutproper service, there would be no consumers, and the business will not be able to achieve itsgoal. For this reason, it’s critical that your service system is of high quality and meets thedemands and preferences of your target audience. Therefore, the purpose of this study is tocollect all relevant data on the service system and determine what is the effect ofenhancement in the service system on customers. In addition, the researchers also aim toprovide reliable information about the new modern service system that will help the currentgeneration and future researchers.The result of this study reveals that the majority of the customers from selected fast foodchains at Sm Fairview are evaluated as "agree" in terms of Taking Orders, ContactlessPayment, Mobile Apps, and Digital Kitchen Board, but there are some variables that came outas the result "disagree" including the Lack of Priority Lanes, On-time Delivery of Foods, andThe food ordered is accurate as what is on the menu board; this study's findings shows themost problem encountered by the customers is the long wait for food delivery and theidenticality of the menu board.The researchers recommend that every fast-food restaurant should install self-service kiosksto eliminate line-ups and improve customer service. Continue to expand priority lanes toguarantee that senior clients do not have to wait too long and that orders are processedquickly. When placing orders, using a coupon is more convenient and may result in moresavings. In terms of the service they provide, clients should be informed that the expected timecan alter when ordering online so that they do not have to wait too long and can plan when toexpect their goods. Fast food establishments should accept e-wallets as payment becausethe bulk of this generation uses them. It is convenient because many older individuals lackknowledge about technology. When they find out how to use it, it is convenient since payingwith an e-wallet ensures that they are charged the correct amount because some older peopledo not know or see the bill they have. Customers are also more likely to make a purchasewhen a fast-food restaurant's menu is well-organized. It becomes more tempting with acomprehensible and attractive menu.
Keywords: Business